Tinjauan Literatur Sistematis Pemodelan ER Untuk Sistem Informasi - Bonie Wijaya; Muhammad Fahrizal; Amaliza Afifah Labib (Jurnal Ilmu Komputer, 2024)
Entity-Relationship (ER) Modeling is a fundamental approach in the design and development of databases for information systems. ER Modeling has long been recognized as an effective conceptual tool for database design. However, with advancements in technology and changing modern data processing needs, several limitations or gaps have emerged in its application, particularly when it comes to handling complex and heterogeneous data. This research presents a systematic literature review using the PRISMA framework to evaluate the development methodologies of ER Modeling in a modern context, including its challenges and opportunities. The main focus includes the adaptation of ER Modeling to technologies such as big data, NoSQL, and cloud computing. Key research issues related to ER Modeling include limitations in handling big data, challenges in representing semi-structured and unstructured data, a lack of support for dynamic data and schema evolution, limitations in integration with modern technologies, and deficiencies in representing complex relationships. The main findings reveal the traditional ER Modeling's limitations in managing complex, semi-structured, and distributed data, as well as the need for integration with modern technologies such as IoT and machine learning. This research contributes by offering insights into the development of more flexible and adaptive ER Modeling for current data needs.